1996
DOI: 10.2737/pnw-gtr-387
|View full text |Cite
|
Sign up to set email alerts
|

Conservation assessment for the northern goshawk in southeast Alaska.

Abstract: The conservation status of northern goshawks in southeast Alaska is examined through developing an understanding of goshawk ecology in relation to past, present, and potential future habitat conditions in the region under the current Tongass land management plan. Forest ecosystem dynamics are described, and a history of forest and goshawk management in the Tongass National Forest is reviewed. Nearly 900,000 acres of the most productive old-growth temperate rain forest in southeast Alaska (public and private la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(72 citation statements)
references
References 65 publications
2
68
2
Order By: Relevance
“…Telemetry studies of Northern Goshawks in southeast Alaska found that females were more likely to remain at low elevations below 250 m, but males, which do most of the hunting while breeding, were found at all elevations in proportion to their availability (Iverson et al 1996). There was, however, relatively little (13%) land above 600 m in this study.…”
Section: Raptors -contrasting
confidence: 49%
See 3 more Smart Citations
“…Telemetry studies of Northern Goshawks in southeast Alaska found that females were more likely to remain at low elevations below 250 m, but males, which do most of the hunting while breeding, were found at all elevations in proportion to their availability (Iverson et al 1996). There was, however, relatively little (13%) land above 600 m in this study.…”
Section: Raptors -contrasting
confidence: 49%
“…Northern Goshawks frequently forage along forest edges (Squires and Reynolds 1997), but telemetry studies in southeast Alaska showed that they did not use edges more frequently than forest interior, relative to the availability of these habitats (Iverson et al 1996). Female goshawks were found within 300 m of beaches more often than expected, but males did not show this pattern.…”
Section: Distribution Of Predators Relative To Fragmentation and Edgementioning
confidence: 73%
See 2 more Smart Citations
“…(Newton 1997) (Reynolds et al 1992) (Greenwald et al 2005) (Bright- Smith & Mannan 1994, Beier & Drennan 1997, Boal et al 2005) (Widen 1989, Drennan & Beier 2003) (Iverson et al 1996) (Kenward 1982) (Rutz 2006 Fig. 1.…”
mentioning
confidence: 99%